RCM Analysis of Process Equipment: A Case Study on Heat Exchanger - A Majid, Mohd Amin; Muhammad, Masdi; Nur IllaniYen@Yem, Nur IllaniYen@Yem (Asian Network for Scientific Information, 2010)
The traditional approach of maintenance emphasis on individual equipment. This practice has caused a number of problems. Among the problems are the maintenance actions are conservative in nature, thinking failure of parts are equals and performing maintenance actions to become totally reactive. Reliability centered maintenance (RCM) was introduced to address these problems. This paper focused on RCM analysis applied to process equipment with heat exchangers as a case study. The seven steps of RCM analysis addressing DEFINE, ANALYSE and ACT are discussed. Results indicate that RCM could assist in identifying the functional failures, causes of failures and risk ranking which are linked to corrosion rates and remaining life of the heat exchangers. Based on the results of the RCM analysis, the next inspec